Reduced Winter‐Time Clear Air Turbulence in the Trans‐Atlantic Region Under Stratospheric Aerosol Injection - K. L. Barnes; A. C. Jones; P. D. Williams; J. M. Haywood (Geophysical Research Letters)
Abstract Clear air turbulence (CAT) is a safety threat within the aviation sector and is projected to worsen under global warming. Stratospheric aerosol injection (SAI) is a climate intervention strategy that aims to ameliorate climate change by artificially cooling Earth. Climate model simulations have found a side‐effect of SAI would be a strengthening of the positive phase of the North Atlantic Oscillation (NAO). This links to a stronger North Atlantic jet stream and suggests enhanced CAT in the region. Here, we analyze simulations from the UKESM1 climate model to evaluate the impact of a realistic SAI application on winter‐time trans‐Atlantic CAT. We find a 23% decrease in severe CAT frequency under SAI when compared to a baseline high‐end global warming scenario. Our results indicate that the amelioration of global warming under SAI has a more dominant impact on CAT over the North Atlantic than residual impacts to the NAO.